Forensic evidence an analysis of shari'ah tests of admissibility - Shalim, K. M. Zakir Hossain Shalim; Haneef, Sayed Sikandar Shah (IIUM Press, International Islamic University Malaysia, 2017)
This study attempts to discuss and examine whether SharÊÑah courts can adopt these common law tests or not. This study used two methods of data collection: library research and opinion survey among the forensic staff of Hospital Kula Lumpur and SharÊÑah experts. This study has reached to a number of findings. The most important among them are: this study proves that common law criteria for forensic evidence are acceptable in admitting forensic evidences in Islamic law as they are justified either by SharÊÑah texts or other standards of evidence in Islamic law; in determining the reliability of science, common law is silent whether the data has been properly collected from the crime scene and preserved; and whether the conclusion given by the expert is correct. Additionally, this study finds that for qualifications of an expert, common law requires knowledge, experiences and training but does not require justness and number of the experts.